PERFORMANCE EVALUATION OF SPRAY COLUMN FOR TOLUENE REMOVAL AS A TAR MODEL FROM A GAS FLOW - Suharto Suharto (Pusbindiklat - LIPI, 2011)
Gasifi cation has become an alternative technology to convert biomass as renewable energy resource. How-ever, the utilization of gas from the process as diesel-engine fuel is hindered by the presence of tar. Used cooking oil could be used as tar absorbent medium due to its higher or nearly equal boiling point compared with that of tar component. In this study, the performance of spray column was evaluated by measuring the absorption effi ciency and mass transfer coeffi cient of volumetric tar in liquid phase (KLa). The tar used in this study was represented by toluene which was carried by air fl ow and then set as tar model in gas producer. The tar model dispersed in air was injected to spray column for absorption process with gas fl ow rate 2.580 L/min and temperature 30°C. The composition of tar model in gas phase was determined both as input and output of spray column by gas chromatography fl ame ionization detector (GC-FID). The absorption effi ciencies of toluene with absorption liquid of water, 5.4% w/w used cooking oil in water and 10.8% w/w used cooking oil in water are 70.2%, 93.8% and 95.2% respectively in 30°C, with KLa value 1.59.10-2/min, 7.10-4/min and 4.10-4/min respectively.